PENGARUH MOTIVASI KERJA DAN KOMPETENSI PROFESIONAL GURU TERHADAP PROSES PEMBELAJARAN DI SMP NEGERI KOTA SEMARANG - Tri Sulasmiyati (STIE Pelita Nusantara Semarang, 2009)
The study deals with the effect of work motivation and teachers’ professional competence on the learning process of state Junior High Schools of Semarang. The problems under study are (1) to what extent is the effect of work motivation on the learning process of State junior High Schools of Semarang, (2) to what extent is the effect of teachers’ professional competenceon the learning process of State Junior Hihg Schools of Semarang, and (3) to what extent is the effect of both work motivation and teachers’ professional competence on the learning process of State Junior High Schools of Semarang.The study adopts a multiple regression analysis. The analysis is used to examine the extent of the effect of work motivation as the independent variable on the learning process as the dependent variable, the extent of the effect of teachers’ professional competence as the independent variable on the learning process of the State Junior High Schools of Semarang, and the extent of the effect of both work motivation and teachers’ professional competence as the independent variables on the learning process as the dependent variable. The sampleconsisted of 206 respondents selected by the use of a proportional stratified random sampling technique and the data were collected by the use of questionnaires.The results of the study show that work motivation significantly affected the learning process of State Junior High Schools of Semarang, indicated by the t-test result of 4.571 which is higher that t-table of 1.660 and had the effect of 31.7%. The teachers’ professional competence significantly affected the learning process of State Junior High Schools of Semarang, indicated by the t-test result of 2.040 which is higher that t-table of 1.660 and had the effect of 28.4%. In addition, both work motivation and teachers’ professional competencesimultaneously and significantly affected the learning process of State Junior High Schools of Semarang, indicated by the F-test result of 12.343 which is higher that the F-table of 3.09 and had the effect of 60.1%.Based on the significant effect of each variable, the teachers of State Junior High Schools of Semarang are suggested to improve their work motivation and professional competence to be able to improve the quality of the teaching-learning process.